2008
DOI: 10.1002/jmri.21298
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of bone scintigraphy, magnetic resonance imaging, and positron emission tomography in bone metastases of myxoid liposarcoma

Abstract: Myxoid liposarcomas (MLS) have a tendency to metastasize to unusual sites. We report an unusual case of bone metastases not detected by bone scan and neither by fluorodeoxyglucose positron emission tomography (PET-FDG) and successfully identified with magnetic resonance imaging (MRI) in a patient with metachronic MLS. Histopathological examination of the primary tumor evidenced a tumor with unfavorable prognostic markers, and the biopsy of an iliac bone lesion confirmed the diagnosis of metastatic disease. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…For the majority of other cancer types, it is a routine procedure for patients during follow-up screening, as it is more sensitive than plain radiographs and CT for finding skeletal metastasis. However, for MLPS, several previous studies reported that skeletal metastasis was detectable by MRI, but not by bone scans (13)(14)(15)(16)(17). In one previous study, based on whole-body MRI findings, 33 MLPS patients were identified with spinal metastases.…”
Section: Discussionmentioning
confidence: 97%
“…For the majority of other cancer types, it is a routine procedure for patients during follow-up screening, as it is more sensitive than plain radiographs and CT for finding skeletal metastasis. However, for MLPS, several previous studies reported that skeletal metastasis was detectable by MRI, but not by bone scans (13)(14)(15)(16)(17). In one previous study, based on whole-body MRI findings, 33 MLPS patients were identified with spinal metastases.…”
Section: Discussionmentioning
confidence: 97%
“…Primary or secondary myxoid tumors often show low accumulation on FDG-PET, such that MRI becomes useful for diagnosis (11)(12)(13)(14)(15). Tateishi et al (7) reported that tumors with a high MIB-1 index tended to have higher accumulation of FDG.…”
Section: Discussionmentioning
confidence: 99%
“…Although it would seem appropriate to increase the yield of PET staging by limiting its use to patients with a higher expected proportion of extrathoracic metastases, this is not necessarily a straightforward proposition. For example, although myxoid liposarcoma is known to have a higher propensity for bony metastases, MRI may be more useful for screening [5]. In the selected clinical scenarios, the PET may be justified despite the low yield because of a large impact on clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…As pulmonary lesions account for approximately 75% of all metastases [3], the utility of adding abdomino-pelvic imaging has been debated [4]. There may be exceptions to this pattern of spread, such as in the case of myxoid or round cell liposarcomas that are known to have a greater propensity for retroperitoneal and bony metastases [5, 6]. …”
Section: Introductionmentioning
confidence: 99%